Marketing Strategy of Educational Services at MAN 3 Jombang - Yuliana, Nurul Intan; Roziqin, Muhamad Khoirur; Darmawan, Moh. Faridl (APPLICATION: Applied science in Learning Research, 2025)
This study aims to describe the marketing strategy of educational services at MAN 3 Jombang in facing competition between educational institutions. The focus of the study includes the characteristics of educational services, market segmentation, implementation of marketing mix (product, price, place, promotion), as well as challenges and innovations carried out to increase the attractiveness of the institution. The approach used is descriptive qualitative with in-depth interview techniques with leaders, teachers, public relations staff, students, prospective students, alumni, and guardians of students. The results of the study show that MAN 3 Jombang integrates general and religious curriculum, with market segmentation that includes students from outside Jombang and promotion through social media and alumni. The marketing mix strategy is implemented comprehensively, with the main products being educational services, scholarship programs, and the Center for Achievement and Innovation (PPI). The challenges faced include limited cost information, digital promotion competition, and teacher time for external promotion. Innovation is carried out through digitalization of services, student involvement in promotional content, and utilization of alumni as promotional agents. In conclusion, the marketing strategy at MAN 3 Jombang is collaborative, creative, and adaptive to the times